STUDY PUBLIC RESPONSE OF SAMARINDA CITY TO THE INSTALLATION OF RAINWATER HARVESTING AND IT’S BENEFITS - Novem Christiandi; Budi Haryanto; Mardewi Jamal (Teknologi Sipil : Jurnal Ilmu Pengetahuan dan Teknologi, 2022)
Flooding, a lack of potable water, and environmental harm caused by regional expansion are all issues that continue to plague Samarinda City. This research tries to persuade the community to use rainwater harvesting (RWH) systems as a solution to these issues, and then closes with the people of Samarinda's overall response. It was discovered that 33% of respondents collect and use rainwater for various reasons utilizing a survey method and descriptive analysis approach. Only 16 percent of the 33 percent use it for basic needs (cooking and drinking water). The majority of responders (80%) think that using rain water (RWH) can lessen the Regional Water Company's service load. However, the number of people who are aware of the favorable effects of RWH on the environment is still quite small, around 25%. The biggest reasons for respondents not installing RWH in their homes and environs are the expense of installation (26%) and space availability (52%) issues. In order to boost public interest in rainwater collecting with RWH installations in the future, more extensive and precise socialization activities and movements are required.